Penerapan Design Thingking Method Pada Sistem Pendukung Keputusan Penerima Bantuan Pemasangan Air Bersih (Studi Kasus : Perumda Tirta Musi Palembang) - Kusmiati, Herlinda; Apriyanty, Desi; Jumriatunnisah, Nur; Ariyani, Resti (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
PERUMDA Tirta Musi Palembang provides assistance to Low-Income Communities (MBR) to install new clean water with several predetermined criteria. In determining the eligibility of recipients of new clean water installation assistance, especially the ranking of assessment results, it is still done manually, where calculations are carried out by grouping data on prospective recipients of assistance based on predetermined criteria, and based on survey results and verification of documents provided by prospective recipients of assistance. So that the decision-making process for recipients of clean water installation assistance takes quite a long time. Decision Support System (DSS) is a system that can be used to help facilitate decision-making by applying decision-making algorithm methods. Simple Additive Weighting (SAW) is one of the algorithm methods that can be used in building DSS by calculating the weighted total of predetermined criteria. In addition, in designing a system, a methodology is needed. Design Thinking Method is a system design approach that can meet the needs and solve user problems by focusing on a deep understanding of system users. The application of the Design Thinking Method in the Design of the SPK for Recipients of Clean Water Installation Assistance at PERUMDA Tirta Musi can facilitate system development in designing a decision-making system.  Keywords— Decision Support System, Simple Additive Weighting (SAW), Design Thingking Method